L'edilizia rurale tra sviluppo tecnologico e tutela del territorio Convegno della II Sezione AIIA Firenze, 20-22 settembre 2012 - Barbari, Matteo; SORBETTI GUERRI, FRANCESCO (Proceedings e report, 2013)
The second Section of the AIIA promoted an opportunity to meet, discuss and reflect on the theme "L'edilizia rurale tra sviluppo tecnologico e tutela del territorio" (Rural construction between technological development and protection of the territory) through the collection of the results of the most recent research conducted on the subject by the SSD researchers " Costruzioni rurali e territorio agroforestale" (Rural constructions and agro-forestry territory). The works included three sessions: in the first part, the results of PRIN 2008 on "Integrazione di sistemi tecnologici innovativi per il monitoraggio a distanza di animali" (Integration of innovative technological systems for remote monitoring of animals) were presented, with interventions by the various Operational Units involved. In the second and third sessions, the scientific results of research on the themes of technological innovation in agricultural buildings and of the Trends in the design of agricultural buildings for a sustainable use of the territory were presented.